DOMINASI PEREMPUAN PEBISNIS DALAM RUMAH TANGGA - Zurani, Ikhma (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2020)
Women as business people are no longer taboo and foreign for at least the past decade. The data shows an increase in the number of women as business people continues to increase from year to year no exception in the city of Pekanbaru. This research aims to find out how women's business domination in the household in Pekanbaru. The study used qualitative techniques with a phenomenological study approach and a constructivism paradigm. Some of the things that became the focus of the analysis in this study: how the dominance of women's decision-making entrepreneurs as wives in households and wife's efforts to preserve family harmony. Decision making in households is divided into three parts, namely: decision making for domestic household affairs; Decision-making in childcare affairs; and other important business decision making. The research results describe if in decision making for domestic affairs of households dominated by wives. Decision-making about parenting is a collaboration between husbands and wives. On the other hand, important decision making involving investment and business is dominated by wives. As a wife, there are several efforts to maintain household harmony including Pillow talk; Realizing the nature of sustenance; and supporting husbands form their own business.